Application of Management Information Systems in F&B MSMEs - Alen Lidia (AGUSPATI RESEARCH INSTITUTA, 2023)
Management information system is an economic device company that supports the business wheel. This system is the support that eases companies to receive information flow where the information flows come from both internal and external companies can be absorbed and presented in a place that is easy to understand, quick, and on target including the current financial information, human resources (HR), marketing and sales strategies that will be built by the company to the issues that will influence business wheel in the company. The aim of this research is to determine the influence of human resource management, electronic systems, and the distribution system in moderation system information for the competitive advantage of UKM in Indonesia.